The Effects of Democratic and Nondemocratic Institutions on CO₂ Emissions - Romy Escher; Melanie Walter-Rogg (Politische Vierteljahresschrift, 2023)
Democratic institutions that coordinate diffuse interests might be beneficial for climate protection. Because the implementation of democratic institutions varies among democracies as well as among autocracies, this study examines whether institutional aspects of different models of democracy affect CO2 emissions in democracies and autocracies. Similar studies have assumed uniform effects of democratic aspects in regimes of both types. The extent of the dependence of autocratic leaders on the support of the ruling party, the military, and/or a~hereditary council might make them less responsive to incentives generated by democratic institutions to reduce CO2 emissions. This article, therefore, examines data on CO2 emissions from 1990 to 2020 in 66~democracies and 69~autocracies separately and analyses whether nondemocratic institutions limit the effects of democratic institutions. As democratic institutions might affect climate outcomes only in the long term, we examine cross-national variation in the long-term development of CO2 emissions and short-term changes in CO2 emissions within countries. In democracies, civil society participation and social equality contribute to a~decrease in the long-term development of CO2 emissions. In autocracies, local and regional democracy contributes to lower CO2 emissions in the long term, and social equality decreases annual changes in CO2 emissions. Military influence limits these effects. In contrast, the dependence of the executive on a~ruling party strengthens the negative effect of social equality on annual changes in CO2 emissions.
Keywords: 320; Climate policy; Democracy; Autocracy; Institutions; Climate change; Social equality; Civil society participation; Klimapolitik; Demokratie; Autokratie; Institutionen; Klimawandel; Soziale Gleichheit; Zivilgesellschaft